1991
DOI: 10.1172/jci115435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cocaine on epicardial coronary artery reactivity in miniature swine after endothelial injury and high cholesterol feeding. In vivo and in vitro analysis.

Abstract: The purpose of this study was to determine the effects of cocaine on vasoreactivity in the swine model. Eight miniature pigs underwent regional endothelial denudation of the left anterior descending coronary artery and were then fed a high cholesterol diet. Cross-sectional area (CSA) of coronary arteries was measured by quantitative angiography. Before denudation, intravenous cocaine (1, 3, and 10 mg/kg) decreased CSA of epicardial vessels by 19-44%. At 3 mo after the denudation, the percent reduction in CSA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…First, cocaine, due to its adrenergic stimulation, causes an increase in heart rate, blood pressure, and LV contractility [129]. Second, documented in several animal studies [98,[130][131][132][133][134][135] is coronary vasoconstriction associated with cocaine use, due to the stimulation of coronary arterial-adrenergic receptors [136,137]. These studies demonstrated that cocaine administered intravenously caused a decrease in coronary artery caliber and decreased coronary blood flow.…”
Section: Cardiovascular Toxicitymentioning
confidence: 96%
“…First, cocaine, due to its adrenergic stimulation, causes an increase in heart rate, blood pressure, and LV contractility [129]. Second, documented in several animal studies [98,[130][131][132][133][134][135] is coronary vasoconstriction associated with cocaine use, due to the stimulation of coronary arterial-adrenergic receptors [136,137]. These studies demonstrated that cocaine administered intravenously caused a decrease in coronary artery caliber and decreased coronary blood flow.…”
Section: Cardiovascular Toxicitymentioning
confidence: 96%
“…First, in vitro studies have reported that adrenergic blockade can influence the effects of cocaine on coronary vascular tone. 13 Increased adrenergic activity has therefore been proposed as an explanation for the effect of cocaine on coronary tone. Also, in vitro evidence suggests that a direct vasodilatory effect of cocaine is apparent at 10-4 mol/L (30 ,ug/mL) concentrations.…”
Section: Coronary Flowmentioning
confidence: 99%
“…Available data in experimental animals suggest that cocaine administration may precipitate myocardial ischaemia either by increasing myocardial oxygen demand, decreasing coronary blood flow, or through a combination of both effects (Hollander & Carter, 1992;Kuhn et al, 1989;Lange et al, 1989). Egashira et al (1991) have shown that cocaine produces a dose-related increase in mean artery pressure (MAP) and heart rate (HR) in miniature swine, whereas we found that cocaine (1, 3 and 10 mg kg-', i.v.) decreases MAP and HR in Yorkshire swine (Nunfiez et al, 1993).…”
Section: Introductionmentioning
confidence: 99%